Development of a Real-Time Gas Concentration Measurement System Using Internet of Things-Based Monitoring - Suhendar, Haris; Indrasari, Widyaningrum; Ghina Muqita, Saffanah; Isnaini, I Gusti Ayu (Program Studi Fisika Universitas Negeri Jakarta, 2024)
Transportation and industrial activities have contributed to an increase in the concentration of pollutant gases such as CO, NO2, and SO2 in the air. High concentrations of these gases can adversely affect human health. One approach to addressing this issue is by measuring and monitoring gas concentrations in the air. The advancement of technology, specifically the Internet of Things (IoT), facilitates the monitoring process. Therefore, this research focuses on the development of a gas concentration measurement system, utilizing the MQ-7 sensor for CO, the MiCS-6814 sensor for NO2, and the MQ-136 sensor for SO2. Additionally, the system is integrated with a website as a platform for monitoring the sensor measurements. The research results indicate that the system has been successfully developed with relative errors of 0.286% for the MQ-7 sensor, 0.325% for the MiCS-6814 sensor, and 0.280% for the MQ-136 sensor. The system underwent testing at three different locations, conducting gas concentration measurements in the environment for 24 hours. The environmental testing revealed measured gas concentration ranges of 2.52-7.67 PPM for CO, 0.00450-0.103 PPM for NO2, and 0.0100-0.0652 PPM for SO2. The measurement data is accessible and observed in real-time through the website, presented in graphical form, indicating average concentration values of CO, NO2, and SO2 over a 3-hour period. Moreover, the website is equipped with indicator lights that serve as alarms if the environmental gas concentration exceeds predefined thresholds.